Tick Bites Induce Anti-α-Gal Antibodies in Dogs - Hodžić, Adnan; Mateos-Hernández, Lourdes; Leschnik, Michael; Alberdi, Pilar; Rego, Ryan O M; Contreras, Marinela; Villar, Margarita; de la Fuente, José; Cabezas-Cruz, Alejandro; Duscher, Georg Gerhard (Vaccines, 2019)
Due to the functional inactivation of the gene encoding for the enzyme that is involved in the oligosaccharide galactose-α-1,3-galactose (α-Gal) synthesis, humans and Old-World primates are able to produce a large amount of antibodies against the glycan epitope. Apart from being involved in the hyperacute organ rejection in humans, anti-α-Gal antibodies have shown a protective effect against some pathogenic agents and an implication in the recently recognized tick-induced mammalian meat allergy. Conversely, non-primate mammals, including dogs, have the ability to synthetize α-Gal and, thus, their immune system is not expected to naturally generate the antibodies toward this self-antigen molecule. However, in the current study, we detected specific IgG, IgM, and IgE antibodies to α-Gal in sera of clinically healthy dogs by an indirect enzyme-linked immunosorbent assay (ELISA) for the first time. Furthermore, in a tick infestation experiment, we showed that bites of Ixodes ricinus induce the immune response to α-Gal in dogs and that the resulting antibodies (IgM) might be protective against Anaplasma phagocytophilum. These findings may help lead to a better understanding of the underlying mechanisms involved in mammalian meat allergy and tick-host-pathogen interactions, but they also open up the question about the possibility that dogs could develop an allergy to mammalian meat after tick bites, similar to that in humans.
Keywords: dog; immune response; tick bite; α-Gal; pathogens; Ixodes ricinus